2009
DOI: 10.1111/j.1742-7843.2008.00339.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Clonidine on Tyrosine Hydroxylase Activity in the Adrenal Medulla and Brain of Spontaneously Hypertensive Rats

Abstract: Abstract:In the present study, we evaluated the effect of the α 2 -adrenoceptor agonist clonidine on tyrosine hydroxylase activity in adrenal medulla and brain of spontaneously hypertensive rats and Wistar Kyoto rats. Six-week-old animals were treated with clonidine (100 μ g/kg body weight, daily, i.p.) for 4 weeks. Treatment with clonidine significantly reduced mean arterial blood pressure in spontaneously hypertensive rats to values similar to normotensive Wistar Kyoto rats. In the adrenal medulla of spontan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…In agreement with our previous reports on catecholamine levels in the adrenal of SHR [20,21], at the start of the collection period (t = 90 min. ), the content of noradrenaline and adrenaline in the adrenal gland was significantly lower in SHR compared with age-matched WKY rats in both ages studied, and there was an age-dependent increase in adrenal catecholamine content ( fig.…”
Section: Animalssupporting
confidence: 93%
See 3 more Smart Citations
“…In agreement with our previous reports on catecholamine levels in the adrenal of SHR [20,21], at the start of the collection period (t = 90 min. ), the content of noradrenaline and adrenaline in the adrenal gland was significantly lower in SHR compared with age-matched WKY rats in both ages studied, and there was an age-dependent increase in adrenal catecholamine content ( fig.…”
Section: Animalssupporting
confidence: 93%
“…However, we have previously shown that in SHR before (6 weeks of age) and during the development of high blood pressure (12 and 22 weeks of age) not only are adrenal catecholamine content and synthesis reduced but also that adrenaline plasma levels are similar compared with those found in the normotensive control Wistar Kyoto (WKY) rats [20]. Moreover, treatment with the a 2 -adrenoceptor agonist clonidine produces a similar reduction in adrenaline plasma levels in SHR compared with WKY rats [21].Despite the importance of a 2 -adrenoceptors in the control of adrenaline release from the adrenal medulla, their role in the control of catecholamine release from the adrenal medulla of SHR during the development of high blood pressure has not been previously tested. Therefore, in this study, we evaluated adrenal a 2 -adrenoceptor function before (6 weeks) and after (16 weeks) the development of hypertension in SHR.…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…Increased noradrenaline synthesis and release and decreased α 2A -adrenoceptor inhibitory function, reflected by elevated noradrenaline plasma levels, are prominent features of SHR hypertension (34 -36). We have recently shown that administration of clonidine to SHR in the pre-hypertensive phase not only reduced sympathetic activation, as evidenced by the reduction in noradrenaline and adrenaline plasma levels, but also completely prevented the rise in blood pressure in the early stages of the development of SHR hypertension (37). We have also previously shown that 12-week-old SHR have significantly higher noradrenaline plasma levels compared to age-matched WKY rats (23).…”
Section: Discussionmentioning
confidence: 88%